Integration of Policy and Technology in Vocational Educational Leadership: A Systematic Literature Review - Mustakim, Waradzi; Giatman, M; Maksum, Hasan; Abdullah, Rijal; Refdinal, Refdinal (Universitas Lampung, 2024)
This systematic literature review examines the integration of policy and technology in vocational educational leadership, focusing on studies published between 2022 and 2024. The review addresses four key research questions: (1) technological tools and advancements supporting leadership in vocational education, (2) the influence of policies and frameworks on leadership strategies, (3) challenges associated with integrating policy and technology, and (4) the socio-economic and educational impacts of this integration. The findings reveal that technological tools such as Learning Management Systems (LMS), digital collaboration platforms, and advanced technologies like Artificial Intelligence (AI) and Virtual Reality (VR) are instrumental in enhancing leadership and educational outcomes. Policies promoting digital transformation, industry alignment, and inclusivity significantly shape leadership strategies. However, challenges like infrastructure limitations and policy-implementation gaps persist. Effective integration of policy and technology in vocational education leads to improved learning environments, better skill acquisition, and enhanced socio-economic outcomes, though ensuring equitable access remains a critical concern. This study provides a comprehensive understanding of how policy and technology intersect to shape vocational education leadership in contemporary settings.Keywords: Vocational Leadership, Policy Integration, Educational Technology, Digital Transformation